Triability or Observability That Influences The Youth Decision Using Mobile Application “Remaja Sehat” ? - Pulung Siswantara1, Muthmainnah1, Riris Diana R1, Astri Meidah S1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Reproductive health of adolescents in Indonesia has become an unresolved priority problem and the number of its cases keep increasing from year to year. It caused by access to information and adolescent health programs that are haven’t been distributed evenly. In fact, not all programs use the media that is in line with the current characteristics of adolescents. Media is an adolescent health promotion strategy that has to be considered in order to increase knowledge. There have been many kinds of media related to adolescent reproductive health in the form of posters, leaflets, public service announcements and so on. According to the previous research, during all this time the media tend to be patronizing and boring. The adolescents nowadays will not be far from gadgets, so researchers have developed “Remaja Sehat” application as a media for adolescent health education. The purpose of this study was to analyze the effect of media on the variables of triability and observability on the decision to use “Remaja Sehat” application.This research was conducted to high school students in Surabaya. The method used in this research is the Quasi Experiment and uses post only design. Samples in this study were 302 conducted by using simple random sampling. The students were given a number of questions in the questionnaire after be given intervention in the form of exposure to a healthy adolescent application. The results showed that there was a significant effect on triability (p value = 0,000) and obsevability (p value = 0.042) on the decision to use “Remaja Sehat” application. Based on this research, it can be concluded that the “Remaja Sehat” application can be used as a media for health promotion which matches the characteristics of adolescents.